1-Phenylisatin - Deepak Shukla; Manju Rajeswaran (Acta Crystallographica Section E, 2011)
In the title compound, C14H9NO2, the phenyl ring makes a dihedral angle of 50.59 (5)° with the mean plane of the isatin fragment. In the crystal, molecules are linked through weak intermolecular C—H...O hydrogen bonds. The crystal structure also exhibits two slipped π–π interactions between the benzene rings of neighbouring molecules [centroid–centroid distance = 3.968 (3) Å, interplanar distance = 3.484 (3) Å and slippage = 1.899 (3) Å], and between the phenyl rings of neighbouring molecules [centroid–centroid distance = 3.968 (3) Å, interplanar distance = 3.638 (3) Å and slippage = 1.584 (3) Å].